Online Customer Contribution Efforts to Increase Customer Satisfaction and Repurchase Intention on Sharia E-Commerce Platforms in Islamic Countries - Galih Ginanjar Saputra; Fadhilah; Halimi Husayn (IAIN Syekh Nurjati Cirebon, 2024)
In the ever-evolving digital era, Sharia e-commerce platforms have become an integral part of Muslim consumers' lives, offering services that prioritize Sharia principles such as contract transparency, product halal compliance, and transactional justice. This study focuses on Sharia e-commerce platforms to investigate the role of Online Customer Experience (OCE) in enhancing Customer Satisfaction and Repurchase Intention. An explanatory research approach was employed with quantitative methods, where data were collected through online questionnaires from 136 active Sharia e-commerce users. Data analysis was conducted using Path Analysis to measure both direct and indirect effects among variables. The study examines OCE as the independent variable, Customer Satisfaction as the intervening variable, and Repurchase Intention as the dependent variable. The findings reveal that OCE elements such as informativeness, entertainment, personalization, social presence, and adherence to Sharia principles significantly influence Customer Satisfaction. Moreover, Customer Satisfaction acts as a mediator affecting Repurchase Intention, where a positive customer experience strengthens loyalty and repurchase intentions. The study emphasizes the importance of Sharia-based customer experience strategies to maintain competitiveness in the e-commerce market. OCE elements integrated with Islamic values have proven to create more satisfying and sustainable customer experiences. These findings provide valuable insights for business practitioners and Sharia e-commerce platform developers in designing services that cater to Muslim consumer needs. By optimizing OCE elements, Sharia e-commerce platforms can reinforce their position as competitive and value-added shopping solutions within the increasingly dynamic digital ecosystem.